Influence of Easy, Speed and Security of Transactions on Decision to Use BRI EDC Machine in Indonesia - Saputra, Rangga Aldiansyah; Fihartini, Yuniarti; Husna, Nurul (Journal of Business Management and Economic Development, 2024)
Technological developments that have occurred to date have led to the birth of payment system innovation in economic transactions. The payment system is no longer done in cash but non-cash. Types of non-cash payments in Indonesia such as phone banking, e-wallet and e-money, internet banking, and payment by credit card and debit card or / ATM card. One method of using a debit card is an EDC machine. Many banks have made EDC machine innovations, one of which is a merchant-specific EDC machine by BRI. The purpose of this study is to determine the influence of the variables of ease of use, transaction speed, and transaction security on the decision to use the EDC machine of BRI merchants in Indonesia. The data used in this study are primary data obtained from the results of respondents' answers collected with the help of questionnaires. The number of samples in this study was 140 respondents. The sample collection method uses purposive sampling, which is a technique used to determine samples with criteria determined by the researcher. The analytical methods used in this study are validity test, reliability test, partial test (T-test), simultaneous test (F test), and coefficient of determination (R20. Then the analysis stage uses multiple linear regression analysis with the help of the SPSS 26 application. The results of this study show that ease of use and security have a significant effect on usage decisions but transaction speed does not have a significant effect on usage decisions.